Talkshow BK: Konseling Pranikah Gen-Z untuk Keluarga Sakinah dalam Islam - Malim Soleh Rambe; Asmaryadi; Harun Ar Rasyid; Siti Salmah; Nurhasanah Pardede (PAKAT: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service program aims to improve the competence of Guidance and Counseling students in premarital counseling based on the integration of psychology and Islamic values ​​for Generation Z (Gen-Z). The background is based on BPS data (2023), which shows 60% of divorces occur in couples under 30, as well as research from the Ministry of Religious Affairs' Research and Development Center (Puslitbang Kemenag) (2022), which identified a lack of understanding of premarital relationships as a major cause of young household failure. The methods used include: (1) Interactive talkshow with multidisciplinary speakers (BK lecturers, psychologists, Islamic marriage practitioners), (2) Role-play simulation based on Islamic Conflict Resolution, (3) Digital platform (Slido, animated video of the story of the Prophet-Khadijah) to increase Gen-Z engagement, (4) Workshop on preparing a sharia premarital checklist. The results show that: 1) Increased understanding of the concept of mawaddah wa rahmah from 45% (pre-test) to 88% (post-test), 2) 82% of BK students were able to design integrative premarital counseling scenarios and 95% of participants considered the interactive method more effective than conventional seminars, 3) Supporting factors include institutional support and suitability of the material to the character of Gen-Z (short visual content 10-15 minutes). The main obstacles were limited discussion time (25% of participants proposed a longer duration) and the sensitivity of topics such as financial infidelity (15% of participants). The implemented solutions included online counseling services via Google Meet and collaboration with the Office of Religious Affairs (KUA) for sensitive topics. This program produced the following outputs: 1) A Gen-Z premarital counseling module, 2) An integrative psychology-Islamic guidebook, 3) Educational YouTube videos and scientific publications. Practical implications include recommendations for: 1) Development of digital content (TikTok/Instagram Reels), 2) Certification of premarital counselors with the KUA, 3) Replication of the program through the National HIMA BK network.